Stakeholder trust and holistic fishery sustainability assessments. (January 2020) - Fleming, Aysha; Ogier, Emily; Hobday, Alistair J.; Thomas, Linda; Hartog, Jason R.; Haas, Bianca
Abstract: Australia is considered world-leading in sustainable fisheries management. Despite this, public perceptions and trust in how fisheries are managed vary widely. Existing models of trust and community acceptance in extractive industries suggest transparently reporting on a wider range of sustainability issues than resource use and condition levels, or the status of target stocks in the case of fisheries, as a potential way to build public awareness and trust. Public perceptions of sustainability can be narrow or broad and related to different world views and perspectives about what is important. Here we investigate whether approaches such as Australia's conceptual 'Healthcheck' framework for fisheries sustainability reporting, could contribute to increasing public trust in fishery management. Interviews with 21 people who currently use (or would use) fisheries information in their professional work revealed interest in a wide range of sustainability issues and a desire for more easily accessible and trusted information. The interviews also revealed four common themes: Trust and distrust; Sustainability concerns and interpretations; Conflicts and values; and Fisheries information sources and knowledge gaps. These themes emphasise the need to take a broad view of sustainability and communication in fishery management, across the range of actors involved, to collaborate widely and build more engagement and relationships with the public in different forms. We use these findings to propose how the established model of trust and community acceptance of natural resource-based sectors could be applied to commercial fisheries and relate to other initiatives, such as the Sustainable Development Goals. Highlights: Building trust through transparency is increasingly important for commercial fisheries to operate. Interviews found that 'sustainability' is multi-dimensional for many stakeholders. A broader view of how to assess sustainability introduces areas of performance beyond those managed by fisheries agencies. Reporting on sustainability across a more holistic set of performance areas could increase trust in commercial fisheries.